Pengalaman Lansia dengan Demensia Ringan-Sedang Dalam Melakukan Komunikasi dengan Pelaku Rawat: Systematic Review - Malikal Balqis, Ummi; Sahar, Junaiti (Jurnal Endurance, 2019)
Dementia is a progressive decline in cognitive abilities that characterized by memory loss that affects everyday abilities. One of the most common problems in elderly with dementia is communication problem. The purpose of this systematic review is to explore the experience of elderly with mild-moderate dementia in communicating with caregivers. This article uses the systematic review method to all selected articles. Through this systematic review approach, six selected themes in phenomenology journals explain that elderly with mild-moderate dementia can describe the symptoms of dementia experienced, feelings of loss and stress caused of dementia, negative stigma towards elderly dementia, loss of control and desire to make their own decisions, and problems in interpersonal relationships. The ability of elderly with mild-moderate dementia in communicating their experiences when interacting with caregivers can be a consideration for caregivers in making decisions related to the condition of their experience in elderly with dementia Demensia merupakan penurunan secara progresif pada kemampuan kognitif yang ditandai dengan kehilangan memori yang mempengaruhi kemampuan sehari-hari. Salah satu masalah yang cukup dominan dirasa pada lansia demensia yaitu masalah di dalam komunikasi. Tujuan dari penulisan ini adalah untuk melihat pengalaman lansia dengan demensia ringan-sedang dalam melakukan komunikasi dengan pelaku rawat. Artikel ini menggunakan metode penulisan systematic review terhadap artikel terpilih. Melalui pendekatan systematic review ini, enam jurnal fenomenologi terpilih menyebutkan bahwa tema-tema yang muncul saat lansia dengan demensia ringan-sedang melakukan komunikasi dengan pelaku rawat, diantaranya lansia mampu untuk menceritakan gejala demensia yang dialami, perasaan kehilangan dan tertekan, stigma negatif orang lain, kehilangan kendali dan keinginan untuk mengambil keputusan sendiri, serta masalah di dalam hubungan interpersonal. Kemampuan lansia dengan demensia ringan-sedang dalam mengungkapkan pengalamannya ketika berinteraksi dengan pelaku rawat dapat menjadi pertimbangan bagi pelaku rawat dalam menentukan keputusan pemberian pelayanan berkaitan dengan kondisi demensia yang dialaminya